The influence of demographic characteristics of hospitality alumni on entrepreneurship factors in Egypt. Issue 2 (3rd April 2019) - Salem, Islam Elbayoumi; Mobarak, Nesma Mostafa
Abstract: The purpose of this article is to study the effect of demographic characteristics of hospitality alumni on entrepreneurship factors, and determine which factors are the most important for the alumni to become entrepreneurs. A questionnaire had been developed and distributed online using Google Forms. Data were collected from 314 hospitality alumni. All the hypotheses have been supported, proving that the investigated demographic characteristics have a significant effect on entrepreneurship factors, particularly motivation, innovation and personal skills. The study's sample was limited to alumni of faculties of tourism and hotels in governmental universities only. Policy-makers implication, practical implication, and social implication are discussed based on the results of this study. This is one of the first studies in Egypt to study the effect of demographic characteristics of hospitality alumni on entrepreneurship. Moreover, it provides significant findings that can enhance the overall status of entrepreneurship in Egypt's hospitality industry.